Penetapan Kadar Genistein Dalam Ekstrak Metanol BijiKedelai Glycine Max L. Merr. Varietas Grobogan MenggunakanMetode KLT Dan HPLC - Retno Aryani; Pudji Astuti; Soekarti Moeljopawiro; Laurentius Hartanto Nugroho (Jurusan Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, 2015)
Soybean (Glycine max L. Merr.) is one of the foodstuffs that are oftenconsumed most of Indonesian. Soy contains phytoestrogens, whichhave chemical structures resemble the hormone estrogen in the body,namely the isoflavones, especially genistein. Genistein is known notonly have various beneficial physiological effects but also act as anendocrine disruptor is because estrogen can play a role as well asantiestrogen activity that affects the metabolism of sex hormones andrelated activities biologi. The objective of this study was to know thequality of genistein in soy extracts Grobogan varieties that have beenpeeled the husk with Thin Layer Chromatography (TLC) and thequantity of soy extract genistein levels Grobogan varieties that havebeen peeled the husk with a method of High Performance LiquidChromatography (HPLC). The method used for extraction ofisoflavones genistein is maceration. Soybean seed samples which havebeen hulled begins with removal of non polar compounds byextraction using n-hexane solvent extraction followed macerationusing 80% methanol. The methanol extract obtained fractionated witha stationary phase of silica gel GF 254, the mobile phase toluene-ethylacetate-aseton- formic acid 20: 4: 2: 1 (v / v). To determine whether ornot a compound genistein compounds in the extract by using acomparison standard genistein further Rf sample extract comparedwith the price of a standard Rf. While the determination of genisteincompound quantitatively with HPLC method genistein standard wear≥ 98% at a concentration of 2, 4, 6, 8, 10 ppm. The identification ofgenistein using Thin Layer Chromatography (TLC), shows the stainsthat have Rf of about 0.43. Results genistein content by HPLC showedpeaks of the chromatograms that have a retention time of about 2,050minutes. HPLC analysis results in three replication showed levels ofgenistein in soya bean varieties Grobogan was 1 g samples of soyextracts that have been flayed husk there was an average of 0.6356 mggenistein. In the soybean seed Grobogan varieties contains isoflavonesgenistein. Levels of genistein in 1 g of sample soy extracts Groboganvarieties that have been flayed epidermis was an average of 0.6356 mggenistein.